2009
DOI: 10.1177/0042085909338686
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Race, Culture, Language, and Disability

Abstract: To date, few researchers have sought to examine the effect of issues of race, culture, language, and disability, let alone to look specifically at the intersection of these issues, as it relates to special education identification, special education service delivery, and students of color's access to an equitable education. Thus, this article will attempt to help urban education researchers and educators understand (a) why the intersection of race, culture, language, and disability is an urban education issue;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(109 citation statements)
references
References 32 publications
1
107
0
1
Order By: Relevance
“…Morrier and Gallagher (2012) reported that children who are minorities were less likely to be identified as having speech or language impairments. These children's underrepresentation possibly results from socioeconomic, linguistic, or cultural obstacles (Blanchett, Klingner, & Harry, 2009;Danesco, 1997;Flores, Tschann, Dimas, Pasch, & de Groat, 2010;García Coll et al, 1996;Harry, 1992;O'Hara, 2003;Peña & Fiestas, 2009). For example, it may be that minority parents are less likely to solicit a professional's evaluation of their children's speech and language difficulties, instead preferring to rely on the advice and support of extended families (García Coll et al, 1996).…”
Section: Early Vocabulary Delays and Later Speech/language Service Usementioning
confidence: 99%
“…Morrier and Gallagher (2012) reported that children who are minorities were less likely to be identified as having speech or language impairments. These children's underrepresentation possibly results from socioeconomic, linguistic, or cultural obstacles (Blanchett, Klingner, & Harry, 2009;Danesco, 1997;Flores, Tschann, Dimas, Pasch, & de Groat, 2010;García Coll et al, 1996;Harry, 1992;O'Hara, 2003;Peña & Fiestas, 2009). For example, it may be that minority parents are less likely to solicit a professional's evaluation of their children's speech and language difficulties, instead preferring to rely on the advice and support of extended families (García Coll et al, 1996).…”
Section: Early Vocabulary Delays and Later Speech/language Service Usementioning
confidence: 99%
“…For students of color with dis/abilities living in urban areas these choices are carried out amid historical and compounding forms of exclusion in public schools (Blanchett, Klingner, & Harry, 2009). Among these inequities, we can include lack of access to the general education curriculum, to meaningful learning experiences due to inadequate personnel and funding resources, and to related services (e.g., speech and occupational therapy, counseling, and social work).…”
Section: School Choice or The Politics Of Desperation? Black And Latimentioning
confidence: 99%
“…The student descriptive statistics results of this study reveal negative minimum The scores of this sample may reflect that Black students with disabilities in urban settings continue to struggle when it comes to receiving quality instruction (Blanchett, Klingner, & Harry, 2009). In addition to the experiences associated with attending urban schools, these students also experience the inequalities of the special education system (Blanchett, 2009).…”
Section: Chapter V Discussionmentioning
confidence: 71%
“…Students that attend urban schools as well as those that are placed in special education share a history laced with undereducation, miseducation, and inequitable treatment by the U.S. education system. Students of color, students with disabilities, and poor schools in urban settings have also experienced a common struggle when it comes to receiving quality instruction (Blanchett, 2009;Blanchett, Klingner, & Harry, 2009). Blacks and other students of color labeled as having a disability often experience double jeopardy: in addition to the experiences associated with attending urban schools and living in poverty, these students also experience the inequalities of the special education system ).…”
Section: Black Students In Urban Special Educationmentioning
confidence: 99%